Determination of metal fatigue of a tower crane using software - Tulekov, Ауезхан; Sazambayeva, Баян; Kenesbek, Ануар; Kenesbek, Инкара (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
This article discusses the application of the finite element method (FEM) to assess the fatigue life of steel structures of tower cranes. By understanding the detrimental effects of cyclic loading, the finite element method allows engineers to model and analyze stress distribution, predict fatigue life, and optimize structures. The article describes the key stages, from structural modeling to stress analysis and fatigue life forecasting, and emphasizes the importance of these methods to improve the safety and reliability of tower cranes. This comprehensive approach is an example of integrating advanced engineering techniques to ensure the durability and reliability of critical construction equipment.